Analysis of the Meaning of Life for Buskers in Jakarta - Mubdiah, Salimatul; Zahra, Nabila Afifa; Palupi, Retno; Wibisono, Dewan Ilyas; Wahyudin, Herul (Prodi Sosiologi Agama, 2024)
The study investigates the lives of street guards in Jakarta, which is a reflection of economic inequality and social dynamics in urban environments. Using qualitative methodologies, the study explores life fertilization in aspects such as life purpose, satisfaction, freedom, attitudes towards death, and suicidal thoughts, all of which are integrated into the broad social, cultural, and economic context. The results revealed that despite limited access to formal education and employment, street guards found ways to survive and give meaning to their lives, highlighting the need for a more empathic and inclusive approach to responding to their needs. These findings encourage the implementation of social policies and interventions that support and appreciate their contribution to city life. The study contributes to a better understanding of street guards in Jakarta and emphasizes the importance of creating urban environments that support their survival and development.